2003
DOI: 10.1530/rep.0.1250175
|View full text |Cite
|
Sign up to set email alerts
|

Motility activation and second messenger signalling in spermatozoa from rat cauda epididymidis

Abstract: This study examined molecular mechanisms involved in the activation of motility in spermatozoa from the cauda epididymidis of rats. A 1.05-fold dilution of semen from the cauda epididymidis with 300 mmol sucrose l −1 did not activate motility in spermatozoa. Addition of dibutyryl cAMP, pentoxifylline or Ca 2+ to the sucrose activated motility in the short term (< 30-60 min). A fivefold dilution of semen from the cauda epididymidis with a modified Tyrode's medium (BWW) activated and sustained vigorous motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…Such motility is regulated by the surrounding environment; obvious changes in motility include activation, hyperactivation, and chemoattraction in various species (Ahmad et al 1995, Ho & Suarez 2001, Wang et al 2001, Wade et al 2003. The cyclic AMP (cAMP)/cAMP-dependent protein kinase A (PKA) signaling pathway and the calcium signaling pathway are generally recognized as the two signaling pathways most central to the regulation of mammalian sperm motility (Brokaw 1987, Wishart & Ashizawa 1987, San Agustin & Witman 1994, Wade et al 2003. Even though the role of these signaling pathways in sperm motility has been demonstrated in many experiments, the specific underlying molecular mechanisms have never been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Such motility is regulated by the surrounding environment; obvious changes in motility include activation, hyperactivation, and chemoattraction in various species (Ahmad et al 1995, Ho & Suarez 2001, Wang et al 2001, Wade et al 2003. The cyclic AMP (cAMP)/cAMP-dependent protein kinase A (PKA) signaling pathway and the calcium signaling pathway are generally recognized as the two signaling pathways most central to the regulation of mammalian sperm motility (Brokaw 1987, Wishart & Ashizawa 1987, San Agustin & Witman 1994, Wade et al 2003. Even though the role of these signaling pathways in sperm motility has been demonstrated in many experiments, the specific underlying molecular mechanisms have never been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Backflushing of the epididymis is traditionally performed using water saturated mineral oil and a balanced salt solution in the syringe itself as a medium to remove the spermatozoa [22][23][24][25] If this occurs, it is impossible to continue and the sample is essentially lost. This can be overcome by the use of BWW or other balanced salt solutions in the syringe, however, although this is successful, we soon recognized that many of the spermatozoa become motile as soon as the BWW solution came into contact and mixed with the caudal epididymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility might be the involvement of cAMP signal transduction pathways. It has been reported that these pathways are involved in activation of sperm motility (Armstrong et al, 1994;Wade et al, 2003). This increase in motility is an important factor affecting fertilization, because high rates of ovum fertilization require efficient transport of sperm from the cervix to the oviducts (Hawk et al, 1978).…”
Section: Discussionmentioning
confidence: 99%